1998
DOI: 10.1111/j.1439-037x.1998.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Studies in Lemongrass (Cymbopogon flexuosus) (Steud. Wats.)

Abstract: Lemongrass (Cymbopogon flexuosus (Steud.) Wats) is a perennial, multicut aromatic grass, which yields an essential oil used in perfumery and pharmaceutical industries and Vitamin A, has a long initial lag phase. To utilize the crop growth resources more efficiently during this phase, studies were made to explore the possibility of intercropping food legumes with lemongrass. An experiment conducted during 1992-93 revealed that the food legumes like blackgram (Viyna mungo (L) Hepper), cowpea {Vigna unguiculata (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The major components of the C. flexuosus oil in the two harvests in this study included citral (75.97–87.70 %), geranyl acetate (0.8–4.91 %), geraniol (0.8–4.26 %), isogeranial (1.83–3.45 %) and isoneral (1.29–2.78 %), which is in line with previously published papers [ 11 , 14 , 57 , 59 , 62 ]. Other compounds were recorded in minimal quantity accounting for less than 0.8 %.…”
Section: Resultssupporting
confidence: 90%
“…The major components of the C. flexuosus oil in the two harvests in this study included citral (75.97–87.70 %), geranyl acetate (0.8–4.91 %), geraniol (0.8–4.26 %), isogeranial (1.83–3.45 %) and isoneral (1.29–2.78 %), which is in line with previously published papers [ 11 , 14 , 57 , 59 , 62 ]. Other compounds were recorded in minimal quantity accounting for less than 0.8 %.…”
Section: Resultssupporting
confidence: 90%
“…Wats.) (Singh and Shivaraj 1998) and vetiver ( Vetiveria zizanioides (L.) Nash.) (Pareek et al 1991) showed that food legumes can successfully be grown as intercrops in the initial lag phase of these crops without adversely affecting the yield of the main crop.…”
Section: Introductionmentioning
confidence: 99%